Organ festivals in the context of sustainable development and heritage interpretation - Bernat, Sebastian (Bulletin of Geography. Socio-economic Series, 2025)
The present study explores the topic of organ festivals/organ music as part of the world's cultural heritage. Its objective is to examine the role of organ festivals in heritage interpretation and sustainability in relation to organ festivals in Poland, including those with an international scope. The method used was a diagnostic survey directed to three social groups: students and research/teaching staff from various research centres in Poland, as well as organisers of organ festivals in Poland. Separate questionnaires were prepared for the audience (students, academics) and the organisers. The study also took into account secondary materials (mainly those available online). In addition to qualitative data, quantitative data was also obtained, thus giving a multi-faceted view of the subject under study. Festivals accessible to the public can not only help to bring forgotten or neglected historic organs back to concert condition or to support the building of new concert-grade instruments, but also to increase the sensitivity of audiences to beauty and stimulate their interest in their cultural heritage (i.e., instruments, venues, music). This requires a proper interpretation of the heritage and an emphasis on the relationship of organ culture with sustainable development.